Diversity, Informant Consensus Factor and Cultural Significance Index of Wild Edible Plants in the Jaunpur region, Tehri Garhwal, Uttarakhand - Dangwal, Lakhi Ram; Lal, Tarseem (Ecological Questions, 2023)
The wild edibles are essential not only for nutrition, medicine, fodder and fuel but also as potential source of income generation. The conventional use of wild edible plants is habitual in the remote and hill regions of the Uttarakhand state (India). The present study was carried out in a mountainous part of the Uttarakhand namely Jaunpur region situated in the district Tehri Garhwal. Extensive field surveys were conducted in the area to gather information (traditional knowledge on wild edible plants) from the inhabitants through questionnaire method. A total of 220 key informants including old aged farmers, shepherds, and vaidyas were surveyed. The present study resulted in documentation of a total 73 plant species (under 58 genera and 38 families) as source of wild edibles. Rosaceae (10 species) and Fabaceae (7 species) revealed as the most dominant families followed by Anacardiaceae, Moraceae and Rutaceae (4 species each). Majority of the recorded species belong to the tree habit (35% species) followed by herb (29%), shrub (29%), and climber (7%). The commonly used plant parts as source of wild edible in the area include fruits (59% species), leaves (24%), seeds (5%) and flowers (4%). Documentation of the traditional knowledge is much important because it provide alternative means to reduce hunger, poverty, and health issues especially in finding novel compounds (drug discovery).